Sensitivity study of different parameters affecting design of the clay blanket in small earthen dams - Alam, Ishtiaq; Ahmad, Irshad (Journal of Himalayan Earth Sciences, 2015)
Dams are structures that retain water for human services. Dams may be earthen, concrete, timber, steel or masonry made. On the basis of size, they may be small, medium and large. The main purpose of a dam is to divert the flow of water for the intended use. Flow of water cannot be stopped permanently even by the best dam ever made. Water may seep from dam body, abutments or the foundation bed below the body of the dam. To control seepage from the foundation bed, certain available methods like cutoff trench, cutoff walls, diaphragms, grout curtains, sheet pile walls and upstream impervious blankets are used. Upstream impervious blankets are considered more economical compared with the other methods mentioned above. The key parameters playing role in blanket efficiency are length of blanket, thickness of blanket, clay core width of the dam, foundation bed depth up to impervious zone, reservoir head, permeability of blanket material and permeability of bed material. This study is focused on the effect of these parameters in seepage control. Seep/W, a finite element method based software is used to model all the mentioned parameters within the individually selected ranges. The results based on the software analysis show that when the length of blanket is gradually increased, the seepage quantity reduces gradually until a specific length where the effect of further increase in length become meaningless. Same is the case for thickness of blanket but in this case the effect is comparatively less. In case of dam's clay core width, before a certain value, it has almost no effect on seepage reduction. Beyond that value, the seepage starts reducing. When the permeable stratum below the dam body is of more depth, the net seepage is more. The permeability of blanket material and foundation material has same pattern of effect on the seepage. In both the cases, when the materials are more pervious, more seepage will be expected from the dam.